2010 IEEE 26th International Conference on Data Engineering (ICDE 2010) 2010
DOI: 10.1109/icde.2010.5447892
|View full text |Cite
|
Sign up to set email alerts
|

Generating code for holistic query evaluation

Abstract: Abstract-We present the application of customized code generation to database query evaluation. The idea is to use a collection of highly efficient code templates and dynamically instantiate them to create query-and hardware-specific source code. The source code is compiled and dynamically linked to the database server for processing. Code generation diminishes the bloat of higher-level programming abstractions necessary for implementing generic, interpreted, SQL query engines. At the same time, the generated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
87
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(88 citation statements)
references
References 11 publications
0
87
0
Order By: Relevance
“…Query compilation is comparable to query plan generation in a relational DBMS, but generates and compiles highly optimized code instead of an operator plan. Previous work [12,16,19,14] has shown that query compilation results in significantly faster query processing than competing interpretative approaches (e.g., tuple-at-a-time) by providing more predictable and register/cache-friendly memory access patterns; more options for the compiler to perform loop-based optimizations; less interpretation overhead per data element; all these enhancements are present in our techniques. Query compilation is also a good fit with in-memory data processing where keeping the CPU(s) busy is one of the key challenges.…”
Section: Overviewmentioning
confidence: 71%
See 1 more Smart Citation
“…Query compilation is comparable to query plan generation in a relational DBMS, but generates and compiles highly optimized code instead of an operator plan. Previous work [12,16,19,14] has shown that query compilation results in significantly faster query processing than competing interpretative approaches (e.g., tuple-at-a-time) by providing more predictable and register/cache-friendly memory access patterns; more options for the compiler to perform loop-based optimizations; less interpretation overhead per data element; all these enhancements are present in our techniques. Query compilation is also a good fit with in-memory data processing where keeping the CPU(s) busy is one of the key challenges.…”
Section: Overviewmentioning
confidence: 71%
“…In this work we explore database-inspired strategies to make query processing on data elements in the managed memory space of a host programming language more efficient by leveraging query compilation [12,16,19]. Query compilation is a highly efficient and easily realisable way to improve the performance of languageintegrated query in managed runtimes.…”
Section: Introductionmentioning
confidence: 99%
“…This interpretation overhead [36,43], stemming from function calls and control flow statements that disrupt the instruction pipeline, affects pipelined query execution negatively. Intuitively, the nested relational algebra operators face similar issues.…”
Section: On-demand Query Enginesmentioning
confidence: 99%
“…Runtime code generation has become an established mechanism, used by several relational engines [6,34,36,43,45,49]. HIQUE [36] generates cache-conscious code via code templates. HyPer [43] uses the LLVM compiler [37] to generate low-level machine code.…”
Section: Related Workmentioning
confidence: 99%
“…To compete with the bulk processing model in terms of CPU efficiency, HyPer relies on JiT-compilation of queries [27]. Whilst DBMS compilers have a long history [3], [8], up to recently [27], [24], [31], the focus has been flexibility and extensibility rather than performance. The idea is to generate code that is directly executable on the host system's CPU.…”
Section: B Partially Decomposed Storage In Hypermentioning
confidence: 99%